2001
DOI: 10.1590/s1519-566x2001000300011
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of the Entomopathogenic Fungi Metarhizium, Beauveria and Paecilomyces in Soybean Under Till and No-till Cultivation Systems

Abstract: e Paecilomyces foi estudada em condições de semeadura direta e convencional da soja. Foi determinada a densidade de unidades formadoras de colônia por g de solo e por cm 2 de folíolos de soja. Verificou-se que no solo sob semeadura direta ocorreu maior incidência dos entomopatógenos, mas sobre os folíolos essa diferença não ocorreu, proporcionando as mesmas possibilidades de infecção nos insetos da parte aérea suscetíveis que ocorrem nas duas condições de cultivo. PALAVRAS-CHAVE: Epizootiologia, Deuteromicetos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
0
10
1
3
Order By: Relevance
“…Agroecosystems suffer from mechanical disturbances due to necessary tillage regimes of various kinds, and these practices may negatively affect occurrence of entomopathogenic fungi in the soil [92,93]. This was confirmed in [72] studies conducted in the years [2002][2003][2004] in the area of Borek Wielkopolski directly adjacent to the "Kościan Plain".…”
Section: Fungimentioning
confidence: 77%
“…Agroecosystems suffer from mechanical disturbances due to necessary tillage regimes of various kinds, and these practices may negatively affect occurrence of entomopathogenic fungi in the soil [92,93]. This was confirmed in [72] studies conducted in the years [2002][2003][2004] in the area of Borek Wielkopolski directly adjacent to the "Kościan Plain".…”
Section: Fungimentioning
confidence: 77%
“…This is a virulent, generalist entomopathogenic fungus that has been reported to infect at least 18 ant species from the Myrmicinae and Formicinae subfamilies, including ants close to the field site of this study, is capable of causing fatal epizootics within colonies, but can also be resisted by ants, depending on their species and group composition amongst other things (Boucias & Pendland, 1998;Schmid-Hempel, 1998;Jaccoud et al, 1999;Hughes et al, 2002Hughes et al, , 2004aPoulsen et al, 2002Poulsen et al, , 2006Lopez & Orduz, 2003;Sumner et al, 2003;Hughes & Boomsma, 2004;Chapuisat et al, 2007;Ugelvig & Cremer, 2007;Reber et al, 2008Reber et al, , 2011Castilho et al, 2010;Ugelvig et al, 2010). Metarhizium is most common in soil, being particularly abundant in the rhizosphere where it can utilise root exudates, but is also found on vegetation (Sosa-Gómez et al, 2001;Meyling & Eilenberg, 2007;St Leger, 2008;Vega et al, 2009;Bruck, 2010). Metarhizium is the asexual anamorph form of the teleomorph ascomycete Metacordyceps, which is also a parasite of ants and other arthropods (Stensrud et al, 2005;Sung et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…The biology of infection through the cuticle, hyphal proliferation within the host insect and semelparous spore production after host death, is therefore similar to some other fungal entomopathogens of ants, such as Beauveria, Aspergillus, and Ophiocordyceps (Boucias & Pendland, 1998;Meyling & Eilenberg, 2007;Hughes et al, 2009;Evans et al, 2011), although Metarhizium is by no means a proxy for them. Metarhizium is most common in soil, being particularly abundant in the rhizosphere where it can utilise root exudates, but is also found on vegetation (Sosa-Gómez et al, 2001;Meyling & Eilenberg, 2007;St Leger, 2008;Vega et al, 2009;Bruck, 2010). It will therefore be encountered by ants during scouting, foraging, waste management and particularly during nest excavation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, more CFUs of EPF are detected per gram of soil from no-tillage systems compared to soils exposed to conventional tillage systems such as ploughing, chiselling and disking (Bing and Lewis 1993;Sosa-Gomez and Moscardi 1994;Hummel et al 2002). Gaugler, Costa, and Lashomb (1989) on the other hand, observed that application of B. bassiana followed by tillage was very important in achieving enhanced fungal persistence in the soil.…”
Section: Agricultural (Cultural) Practicesmentioning
confidence: 99%